Bioresidues of Eugenia fruits as a source of functional ingredients: application in a bakery product - Martins, Bárbara Birck (2022)
Eugenia brasilensis Lam (EB) and Eugenia invoucrata DC (EI are Brazilian fruits that are still little known; however, some local food insustries use these fruits in the confection of frozen pulps and ice creams, processing that can generate bioresidues with no commercial value, but that can have interesting nurtrition value and couls be a source of biocative compounds.